How Does Target-Based Performance Evaluation Affect the Accuracy of Energy-Saving Data: Evidence From China - Zhang, Ping; Yu, Tiantian; Lu, Shengfeng; Huang, Ruting (Frontiers in Energy Research, 2021)
Energy intensity measured by energy consumption per unit of GDP has always been the main assessment indicator for the design of energy saving policies, but its accuracy is highly depended on the reliability of GDP data. This paper finds that the indicator accuracy has been improved after the central government includes energy intensity into the performance appraisal system for local officials. This means that the energy-saving target-based performance evaluation has restrained the data misrepresentation behavior of local officials. Further mechanism analysis shows that the pressure of energy saving restricts the development of industrial sector, which weakens the ability of local governments to manipulate GDP data, thus improving the accuracy of energy intensity statistics. These findings provide some insightful references for China’s future green development and policy design.